1995
DOI: 10.1111/j.1476-5381.1995.tb15020.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA‐induced glutamate and aspartate release from rat cortical pyramidal neurones: evidence for modulation by a 5‐HT1A antagonist

Abstract: 1 We have investigated an aspect of the regulation of cortical pyramidal neurone activity. Microdialysis was used to assess whether topical application of drugs (in 10 M1) to fill a burr hole over the frontal cortex, where part of the corticostriatal pathway originates, would change concentrations of the excitatory amino acids glutamate and aspartate in the striatum of the anaesthetized rat. 2 Topical application of N-methyl-D-aspartate (NMDA, 2 and 20 mM) dose-dependently increased glutamate and aspartate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 39 publications
10
37
0
2
Order By: Relevance
“…While the source of elevated glutamate was not identified in the present study, serotonergic projections from the DRN innervate densely the cortical and allocortical regions supplying glutamate to the accumbens, including the prefrontal cortex, hippocampus, thalamus, and amygdala (eg Vertes, 1991). Indeed, in vivo microdialysis and electrophysiological studies indicate that activation of several different subtypes of 5-HT heteroreceptors in these glutamatergic nuclei can inhibit excitatory neurotransmission (eg Dijk et al, 1995;Cheng et al, 1998;Dawson et al, 2001;Golembiowska and Dziubina, 2002;Hajos et al, 2003), a finding consistent with the observed facilitation of cocaine-induced glutamate release upon DRN inactivation.…”
Section: Serotonin Projections From the Drn Regulate The Acute Effectmentioning
confidence: 62%
“…While the source of elevated glutamate was not identified in the present study, serotonergic projections from the DRN innervate densely the cortical and allocortical regions supplying glutamate to the accumbens, including the prefrontal cortex, hippocampus, thalamus, and amygdala (eg Vertes, 1991). Indeed, in vivo microdialysis and electrophysiological studies indicate that activation of several different subtypes of 5-HT heteroreceptors in these glutamatergic nuclei can inhibit excitatory neurotransmission (eg Dijk et al, 1995;Cheng et al, 1998;Dawson et al, 2001;Golembiowska and Dziubina, 2002;Hajos et al, 2003), a finding consistent with the observed facilitation of cocaine-induced glutamate release upon DRN inactivation.…”
Section: Serotonin Projections From the Drn Regulate The Acute Effectmentioning
confidence: 62%
“…First, it is responsible for further glutamate release, because NMDA receptor blockade reduced the concentration of glutamate in the medium in the period preceding the usual onset of neuronal cell death by 75%. The relevance of this finding is likely to extend to the intact brain because, in rat striatum in vivo, NMDA receptor activation has been shown to evoke delayed glutamate release (Dijk et al, 1995) and ischemiainduced glutamate release is inhibited by NMDA antagonists (Ghribi et al, 1994). Second, NMDA receptor activity represents the dominant mechanism by which NO is generated in the pathological setting, even though several alternative pathways, in principle, could be operative, including non-NMDA receptor activation and nonspecific cellular depolarization (Garthwaite and Garthwaite, 1987;Southam et al, 1991).…”
Section: Roles Of the Nmda Receptormentioning
confidence: 99%
“…At the same time, 5-HT is able to counteract a number of effects mediated by NMDA receptors: for example, NMDA-induced stimulation of 5-HT release from fibers originating in raphe nuclei is inhibited by 5-HT autoreceptors belonging to the 5-HT 1 family [51]. Activation of NMDA receptors in frontal cortex by microdialysis stimulates the release of glutamate in the striatum while reducing local glutamate release, and such effects are inhibited respectively by 5-HT 1A and 5-HT 2A receptors [26,41]. NMDA-mediated NO-synthase activation and cGMP formation in cultured cortical neurons is inhibited by 5-HT 2 receptor agonists [60]; the same effect was observed in cortical slices after application of the 5HT 1B-D agonists sumatriptan and zolmitriptan [172].…”
Section: Modulation Of Glutamate Transmissionmentioning
confidence: 99%